Cystic nephroma and DICER1 mutations: report of a hitherto unreported mutation - Rui Caetano Oliveira; Mónica Jerónimo; Alexandra Paúl; Carol Marinho; Fátima Heitor (Sociedade Brasileira de Patologia Clínica, 2018)
ABSTRACT Paediatric cystic nephroma is a neoplasm of uncertain pathogenesis characterized by a multilocular architecture that develops in children. Some cases may be sporadic, and others may present a familial association, together with other neoplasms, as part of a DICER1 syndrome. We present a case of a paediatric cystic nephroma with an unreported DICER1 mutation and explore the differential diagnosis mainly with cystic partially differentiated nephroblastoma.